2018
DOI: 10.3389/fnmol.2018.00311
|View full text |Cite
|
Sign up to set email alerts
|

Localization of RNAi Machinery to Axonal Branch Points and Growth Cones Is Facilitated by Mitochondria and Is Disrupted in ALS

Abstract: Local protein synthesis in neuronal axons plays an important role in essential spatiotemporal signaling processes; however, the molecular basis for the post-transcriptional regulation controlling this process in axons is still not fully understood. Here we studied the axonal mechanisms underlying the transport and localization of microRNA (miRNA) and the RNAi machinery along the axon. We first identified miRNAs, Dicer, and Argonaute-2 (Ago2) in motor neuron (MN) axons. We then studied the localization of RNAi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 70 publications
(96 reference statements)
4
41
0
Order By: Relevance
“…Dicer is essential for the production of most~22nt active, mature miRNAs from short hairpin precursor miRNAs (pre-miRNAs) (Grishok et al, 2001;Hutvagner et al, 2001). Remarkably, several reports have revealed the presence of Dicer within growth cones (Hengst, 2006;Aschrafi et al, 2008;Zhang et al, 2013;Hancock et al, 2014;Kim et al, 2015;Vargas et al, 2016;Gershoni-Emek et al, 2018). These findings raise the intriguing possibility that inactive pre-miRNAs are trafficked along axons to the growth cone and locally activated to exert their function.…”
Section: Introductionmentioning
confidence: 99%
“…Dicer is essential for the production of most~22nt active, mature miRNAs from short hairpin precursor miRNAs (pre-miRNAs) (Grishok et al, 2001;Hutvagner et al, 2001). Remarkably, several reports have revealed the presence of Dicer within growth cones (Hengst, 2006;Aschrafi et al, 2008;Zhang et al, 2013;Hancock et al, 2014;Kim et al, 2015;Vargas et al, 2016;Gershoni-Emek et al, 2018). These findings raise the intriguing possibility that inactive pre-miRNAs are trafficked along axons to the growth cone and locally activated to exert their function.…”
Section: Introductionmentioning
confidence: 99%
“…Dicer and pre-miRNAs are present within axons Numerous studies have reported the presence of Dicer within mammalian growth cones by immunofluorescence in culture (Aschrafi et al, 2008;Gershoni-Emek et al, 2018;Hancock et al, 2014;Hengst et al, 2006;Kim et al, 2015b;Vargas et al, 2016;Zhang et al, 2013) , but whether Dicer is also detected in the growth cones of lower vertebrates such as Xenopus laevis is so far unknown. We thus examined the distribution of Dicer in RGC axons in this species (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Dicer is a key component of the miRNA-induced silencing complex (miRISC) which is essential for the production of~22 nt active, mature miRNAs from hairpin precursor miRNAs (pre-miRNAs) (Grishok et al, 2001;Hutvagner et al, 2001) . Remarkably, numerous reports have revealed the presence of Dicer within growth cones (Aschrafi et al, 2008;Gershoni-Emek et al, 2018;Hancock et al, 2014;Hengst et al, 2006;Kim et al, 2015b;Vargas et al, 2016;Zhang et al, 2013) . These findings raise the intriguing possibility that inactive pre-miRNAs are trafficked along axons to the growth cone and locally processed for function.…”
mentioning
confidence: 99%
“…In fact, miRISC protein GW182 was first identified from the serum auto-antibodies of patients with neuropathic symptoms (Eystathioy et al, 2002(Eystathioy et al, , 2003, and changes in its levels are implicated in Alzheimer's disease (Rouillard et al, 2016;Badhwar et al, 2017). Altered localization and trafficking of miRISC was recently reported in a cell culture model of amyotrophic lateral sclerosis (ALS) (Gershoni-Emek et al, 2018). Moreover, recent studies highlighting the interactions of miRISC components with proteins involved in neurodegenerative disorders, such as HTT, FUS, and Ataxin points toward an important role of miRISC composition in the pathology of these disease which should be investigated in detail (Savas et al, 2008;McCann et al, 2011;Zhang T. et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple components of miRISC machinery are shown to localize in developing axons and growth cones (Hengst et al, 2006;Murashov et al, 2007;Dajas-Bailador et al, 2012). A recent study has shown the co-localization of core miRISC (AGO2 and miRNAs) with mitochondria at axonal branch points and growth cone of peripheral nerve axons (Gershoni-Emek et al, 2018). miRISC protein FMRP has been shown to regulate Semaphorin 3A mediated growth cone collapse (Li, 2009).…”
Section: Polarization and Neurite Growthmentioning
confidence: 99%